AN ANALYSIS OF TARZAN’ LANGUAGE ACQUISITION IN THE MOVIE TARZAN OF THE APES (1999) (NOBEL: Journal of Literature and Language Teaching, 2015)
This study concerns to the analysis of language acquisition in the movie Tarzan of Apes (1999). The study focuses on the character of Tarzan, how his own language is and how he passes his process of language acquisition. The study is descriptive qualitative because this study describes the process of language acquisition in the movie of Tarzan of the Apes. The writer uses some theories about language acquisition from Noam Chomsky, B.F. Skinner and some other supporting theories to conduct this study. By this study, the writer finds that Tarzan has no language until he meets other humans because he does not have supporting environment to get language acquisition. He is able to communicate with animals and vocalizes some sounds. Tarzan begins his language acquisition after he meets other humans.